From screen to ground: Pandawara Group's strategy in reserving Indonesia's environment - Zuliansyah, Zulmi; Jatmika, Sidik (Faculty of Communications Science, Dr. Soetomo University, 2025)
This article focused on analysing the strategy and impact of the Pandawara Group in encouraging environmental conservation efforts in Indonesia. The study used a qualitative method to analyse and interpret phenomena within this research, incorporating data on engagement metrics such as likes, views, and followers for each organisation's social media accounts, which were collected using SocialBlade. The findings of this study show that Pandawara Group's activities have successfully increased public awareness of environmental issues. This is reflected in the high engagement and positive sentiment revolving around their environmental content on social media. Moreover, their campaigns have inspired collective action, as evidenced by the growing number of communities participating in their clean-up activities. Despite these achievements, several challenges persist. Ensuring the sustainability of community engagement in environmental protection remains a significant hurdle. Additionally, the government's role in addressing environmental pollution requires further attention. This article offers a new approach to the environmental movement in Indonesia, specifically on optimising digital media to build public awareness and encourage collective action for environmental conservation.